A Heterogeneous Niobium(V) Oxide Catalyst for the Direct Amidation of Esters. Issue 17 (11th August 2015) - Ali, Md. Ayub; Siddiki, S. M. A. Hakim; Kon, Kenichi; Shimizu, Ken‐ichi
Abstract This study reports the first example of a heterogeneous catalytic system for the direct amidation of various esters with amines. Of 25 types of catalyst, Nb2O5 shows the highest activity in the amidation of methyl benzoate with aniline. Nb2O5 gives high yields in the amidation of various esters and amines under solvent‐free conditions, is reusable, and shows higher turnover numbers than previously reported homogeneous catalysts such as La(OTf)3. IR spectroscopic studies of ethyl acetate adsorbed on the catalysts show a strong acid–base interaction between the Nb5+ Lewis acid site and carbonyl oxygen, which can result in high reactivity of the ester with a nucleophile (amine) and, thus, high activity of Nb2O5. Kinetic results show that the activity of Nb2O5 does not markedly decrease with increasing aniline concentration, in contrast to reference catalysts TiO2 and La(OTf)3. The relatively low negative impact of basic molecules on the Lewis acid catalysis of Nb2O5 also enables its high activity.